(untitled) (Texas Journal of Medical Science, 2026)
Metabolic syndrome is a dangerous complex of metabolic disorders characterized by insulin resistance (decreased tissue sensitivity to insulin). This condition greatly increases the risk of developing type 2 diabetes, heart attack, and stroke. The aim of the study was to investigate the impact of metabolic syndrome on the development of endocrine and cardiovascular diseases. Clinical and laboratory parameters of patients with metabolic syndrome were analyzed. The findings demonstrated that the presence of metabolic syndrome is associated with a high prevalence of type 2 diabetes mellitus, arterial hypertension, and coronary heart disease. Statistically significant correlations were identified between body mass index, waist circumference, blood glucose levels, and indicators of cardiovascular risk